2021
DOI: 10.34133/2021/9525802
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Donor-Resonance-Donor Molecules for Acceptor-Free Bipolar Organic Semiconductors

Abstract: Organic semiconductors with bipolar transporting character are highly attractive as they offer the possibility to achieve high optoelectronic performance in simple device structures. However, the continual efforts in preparing bipolar materials are focusing on donor-acceptor (D-A) architectures by introducing both electron-donating and electron-withdrawing units into one molecule in static molecular design principles. Here, we report a dynamic approach to construct bipolar materials using only electron-donatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…To experimentally verify our strategy for constructing stimuli-responsive OURTP materials, two resonance molecules of P , P -di­(9 H -carbazol-9-yl)- N , N -diethylphosphinic amide ( DECzPO ) and P , P -di­(9 H -carbazol-9-yl)- N , N -diethylphosphinothioic amide ( DECzPS ) with resonance bridges of N–PO and N–PS were designed and facilely prepared in high yields . Additionally, 1,1-di­(9 H -carbazol-9-yl)- N , N -diethylphosphanamine ( DECzP ) was also synthesized for comparison investigations to understand the inherent impact of E RV on the photoactivated properties of stimuli-responsive OURTP materials.…”
Section: Resultsmentioning
confidence: 99%
“…To experimentally verify our strategy for constructing stimuli-responsive OURTP materials, two resonance molecules of P , P -di­(9 H -carbazol-9-yl)- N , N -diethylphosphinic amide ( DECzPO ) and P , P -di­(9 H -carbazol-9-yl)- N , N -diethylphosphinothioic amide ( DECzPS ) with resonance bridges of N–PO and N–PS were designed and facilely prepared in high yields . Additionally, 1,1-di­(9 H -carbazol-9-yl)- N , N -diethylphosphanamine ( DECzP ) was also synthesized for comparison investigations to understand the inherent impact of E RV on the photoactivated properties of stimuli-responsive OURTP materials.…”
Section: Resultsmentioning
confidence: 99%
“…These molecules can be facilely prepared in three steps: (1) the reaction of carbazolyl borate with bromotriphenylethylene by Suzuki cross-coupling gives the triphenylvinyl-carbazole (TPE-Cz) precursor in a yield of 72%; (2) TPE-Cz is lithiated with n-butyl lithium under a nitrogen atmosphere at À78 1C, and then reacts with diphenylphosphine chloride to produce TPE-P (yield: 75%); (3) TPE-P is then oxidized or sulfurated by hydrogen peroxide or sulfur without any catalyst under atmospheric conditions to produce TPE-PO or TPE-PS with the yields of 90% and 87%, respectively (Scheme S1, ESI †). 17 Their chemical structures were fully confirmed by 1 H NMR, 13 C NMR and high resolution mass spectra (Fig. S1-S11, ESI †).…”
Section: Molecular Design Synthesis and Characterizationmentioning
confidence: 87%
“…14 A series of organic resonance molecules containing N-PQX (X = O, S, or Se) or N-CQO resonance structures were developed based on donor-resonance-acceptor or donor-resonance-donor architectures. [14][15][16][17][18] Owing to the facile resonance variation in realizing the dynamically balanced charge transport, the external quantum efficiencies (EQEs) of the blue and white phosphorescent OLEDs employing these resonance molecules as host materials show high values of up to 31.2% 18 and 23.5%, 19 respectively; the EQEs of the blue and green thermally activated delayed fluorescence OLEDs reach 20.5% 18 and 15%, respectively. 14 Furthermore, the intersystem crossing (ISC) process from the excited singlet to triplet states can be significantly promoted by virtue of the varied excited-state energies of resonance canonical forms for reducing the real-time splitting energy between the lowest singlet and triplet states, resulting in simultaneously elongated organic afterglow lifetime and improved efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Excitingly, organic semiconductors having resonance linkages are capable of showing dynamically variable tautomerization between neutral and charged resonance forms for charge redistribution (Figure a), thus leading to the selective evoking of optimal electrical properties without any adverse influence on the optical attributes and providing a new way for search and design of optoelectronic materials with purposefully regulated properties. Also, it has been manifested that the resonance molecules with more enantiotropic resonances (Figure a, bottom) demonstrate enhanced dynamic adaption ability to achieve boosted electronic properties compared to those with less enantiotropic resonance (Figure a, top) due to their more dynamic canonical form to improve the possibility for the presence of these charged forms to enable the construction of the dynamic carrier transporting channels. Experimentally, the maximum external quantum efficiency (EQE) of blue phosphorescent devices was 16.5% using typical D–r–A-type hosts with enantiotropic N + P–O – resonances; and through resonance engineering, a D–r–A-type host with enantiotropic N + P–S – resonances was developed and the EQE of its blue PhOLED could be increased to 21.3%. , These results indicated that through rational resonance linkage and engineering, the eventual device performance hosted by resonance molecules can be efficiently improved.…”
Section: Introductionmentioning
confidence: 99%